2018
DOI: 10.21608/ejhc.2018.13943
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Providers’ Awareness Regarding Quality Management System and Its Relation to Patient Satisfaction

Abstract: Introduction: quality is emerging as a dominant and complex theme in today's competitive health care environment; it plays an important role in patients' choice of hospital. Quality of care is partly a function of the need for care and includes patients' satisfaction which is a function consistent with scientific knowledge and generally accepted professional standards. Aim: the present study aimed to assessing health care providers' awareness regarding quality management system and it's relation to patient sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Gupta et al (2017) showed that management leadership, one of the dimensions of total quality management, stimulated innovation performance in Indian firms. Abdallah and Mohamed (2018) indicated a substantial favourable connection between total quality management mindfulness and satisfaction of patients using data from caregivers in Egypt. Abadi et al (2018) also discovered that total quality management favourably contributed to the satisfaction of 398 patients in Indonesia.…”
Section: Theoretical Development Resource-based Theory Of a Firmmentioning
confidence: 99%
See 2 more Smart Citations
“…Gupta et al (2017) showed that management leadership, one of the dimensions of total quality management, stimulated innovation performance in Indian firms. Abdallah and Mohamed (2018) indicated a substantial favourable connection between total quality management mindfulness and satisfaction of patients using data from caregivers in Egypt. Abadi et al (2018) also discovered that total quality management favourably contributed to the satisfaction of 398 patients in Indonesia.…”
Section: Theoretical Development Resource-based Theory Of a Firmmentioning
confidence: 99%
“…In addition, literature addressing the mechanism through which a quality management strategy passes to boost innovative performance in firms have gone unnoticed. Existing studies have concentrated on the effect total quality management on variables like patient satisfaction (Abadi et al, 2018;Abdallah and Mohamed, 2018;Zaid et al, 2020), student retention (Koomson, 2022), sustainable performance (Akanmu et al, 2020), procurement performance (Kingi and Mwangangi, 2017), organisational performance (Kura et al, 2020;Sawaean and Ali, 2020;Sweis et al, 2019;Thai and Jie, 2018), corporate social performance, financial and market performance (Sila, 2018), productivity (Mosadeghrad and Afshari, 2020), competitive advantage (Ali, 2020;Othman et al, 2020), knowledge creation (Barua, 2021), academic performance (Sweis et al, 2020), business value excellence (Alomari et al, 2020), market orientation and service quality (Samat et al, 2006), flexible performance (Phan et al, 2019), integrated performance (Udofia et al, 2021) and operational performance (Kumar and Mishra, 2020), overlooking innovative behaviour and innovation performance. Hence, in this conceptual piece, we address the effect of total quality management on innovation performance in the banking sector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of the proposed positive relationship between TQM and student LOY, Abdallah and Mohamed (2018) uncover a strong positive correlation between healthcare providers’ awareness of TQM and patient satisfaction. Abadi et al.…”
Section: Introductionmentioning
confidence: 70%
“…Abadi et al (2018) augmented that total quality management positively contributed to patient satisfaction among 398 patients in Indonesia. Abdallah and Mohamed (2018) showed a strong positive correlation between healthcare providers' awareness of total quality management and patient satisfaction in Benha Family Centres in Egypt. Nguyen and Nagase (2020) also found support for a positive relationship between total quality management and satisfaction among inpatients undergoing treatment at a tertiary-level hospital in Vietnam.…”
Section: Theoretical Developmentmentioning
confidence: 94%